Insights from coral microatolls into sea-level variability and subduction zone behavior - Sarkawi, Gina Muthia (Nanyang Technological University, 2024)
An understanding of the processes driving relative sea-level (RSL) changes is necessary for coastal adaptation and risk assessments. Coral microatolls form in the intertidal zone as coral colonies whose upward growth is limited to low water levels making it a useful proxy for understanding relative sea level (RSL) changes; a combination of both sea-level and land-level changes. We investigate coral microatoll records across Southeast Asia to better understand drivers of RSL and assess earthquake potential in regions with limited observations. I examine a living coral microatoll from western Luzon, Philippines to determine what sea level and atmospheric drivers control coral microatolls in the region. Using a RSL record from 1906 – 2018 CE, we establish the relationship of living coral microatolls to low water levels, 27 ± 12 cm above extreme low water, and find that coral deaths are controlled by El Niño events during non-tectonic episodes. I analyze fossil coral microatolls from the same site to ascertain any tectonic hazard for the region. Two generations of fossil coral microatolls were analyzed, one from 1000 calibrated years before present and the younger fossil generation from the 19th century. Two instances of coseismic subsidence of on the order of ≥ 38 cm and one coseismic uplift ≥ 45 cm were determined from the record. We use forward elastic dislocation models to determine potential causative faults that could produce vertical deformation seen in the coral record. Lastly, I compile published fossil coral microatoll records across Simeulue Island, Indonesia to investigate the size of two paleoearthquakes, the 1394 CE and the 1450 CE, which were predecessor ruptures to the Mw 9.2 2004 CE Aceh-Andaman earthquake. The high uplift recorded from the corals led to the assumption that larger earthquakes have occurred on the same rupture patch. Through elastic dislocation models, we present models that indicate the 1394 and 1450 CE earthquakes could be smaller than the 2004 earthquake assuming a range of plausible rupture parameters.